Productivity of Ber Based Hortipastoral System on Red Alfisol: Effect of Pruning Intensities and Pasture Combinations - Kumar, Sunil; Ram, S.N.; Baig, M.J.; Roy, M.M. (Indian Journal of Agroforestry, 2020)
The experiment was conducted on a 10-year-old Ber plantation at C R Farm, Indian Grassland and Fodder Research Institute, Jhansi during 2001-2003 with 3 levels of pruning and 4 pasture combinations. The result indicated that severely pruned tree produced significantly lower fruit yield in both years as compared to medium and light pruned tree. The light pruned tree produced significantly higher fuelwood as compared to severely pruned tree. The fruit length, diameter and weight was influenced with pruning, medium pruned tree produced better quality fruits. The total soluble solids (TSS), acidity were neither influenced with pruning nor with pasture combinations. The ascorbic acid (vitamin C) content did not show any definite trend with variation in pruning intensities. The maximum forage production was recorded with severe pruned tree. The average fruit yield and quality was found better in first year than second year due to good rainfall and rainy days in first year as compared to second year. Among pasture combination, Guinea grass + Stylo produced significantly higher yield as compared to Guinea + Dinanath + Stylo, Dinanath + Stylo and natural pasture. The maximum fruit yield (27.81 kg/tree) was recorded under natural conditions as compared to sown pasture.